1993
DOI: 10.1111/j.1476-5381.1993.tb13836.x
|View full text |Cite
|
Sign up to set email alerts
|

Human liver microsomal metabolism of the enantiomers of warfarin and acenocoumarol: P450 isozyme diversity determines the differences in their pharmacokinetics

Abstract: 1 To explain the large differences in (the stereoselectivity of) the clearances of the enantiomers of warfarin and acenocoumarol (4'-nitrowarfarin) their human liver microsomal metabolism has been studied and enzyme kinetic parameters determined. The effects of cimetidine, propafenone, sulphaphenazole, and omeprazole on their metabolism has been investigated. 2 The 4-hydroxycoumarins follow similar metabolic routes and are mainly hydroxylated at the 6-and 7-position (accounting for 63 to 99% of the metabolic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
37
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 32 publications
(47 reference statements)
2
37
2
Order By: Relevance
“…The difference in structure of acenocoumarol and phenprocoumon, although small, may have implications on the relative contribution of CYP enzymes to their metabolism [6]. Therefore, the risk of bleeding associated with the start of inhibitors of CYP1A2, 2C19, and 2C9 possibly differs with the type of anticoagulant used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in structure of acenocoumarol and phenprocoumon, although small, may have implications on the relative contribution of CYP enzymes to their metabolism [6]. Therefore, the risk of bleeding associated with the start of inhibitors of CYP1A2, 2C19, and 2C9 possibly differs with the type of anticoagulant used.…”
Section: Discussionmentioning
confidence: 99%
“…First, pharmacodynamic interactions with one anticoagulant may well apply to another anticoagulant [18]. Second, PIDs that interact by inhibiting CYP2C9 will affect both acenocoumarol and warfarin [6]. Third, PIDs that do not influence the intensity of the anticoagulant effect of coumarin anticoagulants, but increase the risk of bleeding by interfering with hemostasis or by their ulcerogenic effect, will exert their effect regardless of the type of coumarin used.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, warfarin is eliminated almost entirely by hepatic metabolism, mainly through cytochrome P450 isoenzymes. S-warfarin is hydroxylated by CYP2C9, whereas R-warfarin is metabolized mainly through the CYP1A2 enzyme [2]. As the S-enantiomer is the more potent of the two, interactions with the CYP2C9 isoenzyme may result in a clinically significant interaction [3].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that cytochrome P450 2C9 (CYP2C9) and vitamin K epoxide reductase complex 1 (VKORC1) gene polymorphisms are significantly associated with warfarin sensitivity (2)(3)(4)(5), including among Asian patients. Several dosing guidelines and algorithms based on genetic data have been proposed in response to reports that the addition of genetic data into a nongenetic dosing model may increase the predictability of the model by up to 16% (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%